The Effect of Employer Branding and Corporate Reputation on Intention to Apply via Work Expectation - Widiantari, Kadek; Irma Yunita, Putu (Universitas Pamulang, 2025)
Human Resources (HR) play a strategic role in determining a company’s success, especially in facing global competition that demands high levels of creativity and innovation. Generation Z, as a productive age group characterized as digital natives, now dominates the labor market, including in the Province of Bali. However, companies still face challenges in attracting the interest of this generation to apply for jobs. This study aims to analyze the effect of employer branding and corporate reputation on intention to apply with work expectation as a mediating variable among Generation Z in Bali Province. This research employs a quantitative approach using the Structural Equation Modelling–Partial Least Squares (SEM–PLS) method through the SmartPLS version 4.0 application. The research sample consists of 130 respondents selected using a purposive sampling technique, with criteria of individuals born between 1997–2012 who are currently seeking employment. The results indicate that employer branding (β = 0.192; p < 0.05) and corporate reputation (β = 0.284; p < 0.01) have a positive and significant effect on intention to apply, with an R² value of 0.56. In addition, employer branding (β = 0.498; p < 0.001) and corporate reputation (β = 0.384; p < 0.001) significantly influence work expectation, which in turn also affects intention to apply (β = 0.427; p < 0.001). These findings indicate that work expectation acts as a partial mediator in the relationship between employer branding and corporate reputation toward intention to apply. The implications of this study emphasize the importance of strengthening the company’s image and building a positive reputation to attract and retain Generation Z talents in Bali through the management of work expectations that align with the needs of this generation.